BLOCKCHAIN INTEGRATION IN THE FINANCIAL INDUSTRY:OPPORTUNITIES AND CHALLENGES BASED ON LITERATURE REVIEW - Fittry Megasari Sijabat (CV. Adiba Aisha Amira, 2024)
This research aims to explore the opportunities and challenges of integrating blockchain technology in the financial industry through a comprehensive literature review. Blockchain promises to improve efficiency, transparency, and security in various financial processes, including reduced transaction costs and accelerated settlement. However, its implementation is faced with various challenges, such as scalability issues, regulatory uncertainty, and the need for security sustainability. This study finds that while the potential of this technology is great, the full realisation of its benefits requires a strategic approach, clear regulations, and collaboration between stakeholders. This study is expected to provide greater insight into how blockchain can be effectively adopted in the financial industry, as well as the steps needed to overcome the existing barriers.